P025 Disturbed sexual functioning in female patients with systemic sclerosis. (March 2019) - Hermankova, B; Spiritovic, M; Smucrova, H; Oreska, S; Storkanova, H; Pavelka, K; Vencovsky, J; Senolt, L; Becvar, R; Tomcik, M
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Systemic sclerosis (SSc) is a chronic autoimmune disease leading to various physical and psychological impairments including sexual dysfunction. Objectives: The aim of this study was to assess sexual functions/quality of life and pelvic floor function in female SSc patients compared to age-/sex-matched healthy controls (HC), and to analyze the potential impact of disease activity, fatigue, physical activity and depression. Methods: In total, 41 women with SSc (mean age: 50.9, disease duration: 5.8 years, lcSSc/dcSSc: 18/23, mRSS: 13.6, ESSG activity index: 2.5), who fulfilled the ACR/EULAR 2013 criteria, and 41 healthy controls (mean age: 50.9) without rheumatic diseases filled in 12 well-established and validated questionnaires assessing sexual function/quality of life, pelvic floor function, fatigue, physical activity and depression. We used the following questionnaires: Female Sexual Function Index (FSFI), Brief Index of Sexual Function for Women (BISF-W), Sexual Quality of Life Questionnaire (SQoL-F), Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12), Pelvic Floor Distress Inventory Questionnaire (PFIQ7), Fatigue Impact Scale (FIS), Beck's Depression Inventory II (BDI II), Health Assessment Questionnaire (HAQ), Scleroderma Health Assessment Questionnaire (SHAQ) and Human Activity Profile (HAP). Results: Compared to HC, patients with SSc had significantly higher prevalence and greater severity of sexual dysfunction (FSFI, BISF-W: in all subscales as well as total scores), dysfunction of pelvic floor (PISQ-12, PFIQ7), and worse sexual quality of life (SQol-F) (table). Worse scores in SSc patients were associated with higher disease activity [ESSG activity index: SQol-F (r=−0.364, p=0.0443)], greater fatigue [FIS correlated negatively with both FSFI, and BISF-W], more severe depression [BDI-II: FSFI (r=−0.553, p=0.0002), BISF-W (r=−0.514, p=0.0007)], deteriorated quality of life [SHAQ: FSFI (r=−0.536, p=0.0003), BISF-W (r=−0.563, p=0.0001), SQol-F (r=−0.338, p=0.0382), PISQ-12 (r=0.563, p=0.0051)], and worse ability to perform physical activities [HAP: FSFI (r=0.407, p=0.0082), BISF-W (r=0.409, p=0.0078)]. Conclusions: Women with SSc reported significantly impaired sexual function, sexual quality of life and pelvic floor function than age-matched healthy controls. Worse scores in SSc were associated with disease activity, physical activity, fatigue, depression and quality of life. Acknowledgements: Supported by AZV-16-33574A, MHCR 023728, and SVV – 2 60 373. Disclosure of Interest: None declared.